2016
DOI: 10.1111/bjd.14634
|View full text |Cite
|
Sign up to set email alerts
|

A phase I randomized trial to assess the effect on skin infiltrate thickness and tolerability of topical phosphodiesterase inhibitors in the treatment of psoriasis vulgaris using a modified psoriasis plaque test

Abstract: Topical treatment with cream formulations of the PDE4 inhibitors roflumilast and TAK-084 reduced inflammation, measured as a change in skin infiltrate thickness, and reduced psoriasis severity. Corticosteroid treatments have known systemic and cutaneous side-effects; PDE4 inhibitors could offer an alternative to these and deserve further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
(36 reference statements)
1
7
0
Order By: Relevance
“…The psoriasis plaque test model allows for the simultaneous topical treatment of multiple drugs/formulations within the same plaque for intra-individual comparison. 4 Participants were treated with 200 lL of GSK2981278 ointment (0Á03%, 0Á1%, 0Á8% or 4%), vehicle and betamethasone valerate 0Á1% cream (positive control) once daily excluding Sundays. All participants received all six study treatments randomly assigned to individual test fields.…”
Section: Research Lettermentioning
confidence: 99%
“…The psoriasis plaque test model allows for the simultaneous topical treatment of multiple drugs/formulations within the same plaque for intra-individual comparison. 4 Participants were treated with 200 lL of GSK2981278 ointment (0Á03%, 0Á1%, 0Á8% or 4%), vehicle and betamethasone valerate 0Á1% cream (positive control) once daily excluding Sundays. All participants received all six study treatments randomly assigned to individual test fields.…”
Section: Research Lettermentioning
confidence: 99%
“…In two clinical studies involving 352 and 844 patients with active psoriasis, apremilast was found to be effective in treating moderate to severe plaque psoriasis [46,47]. In another small clinical study, the PDE4 inhibitor roflumilast, which is an oral drug approved for the treatment of COPD, reduced severity of psoriatic lesions [48]. Interestingly, data from Moretto et al 2015 suggested that CHF6001, which is currently undergoing clinical trials as an inhaled agent in COPD, is about 10fold more potent in inhibiting all four isoforms of PDE4 than roflumilast and in eliciting antiinflammatory effects as well [7].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to tapinarof, the decreased risk of adverse events of phosphodiesterase 4 (PDE‐4) inhibitors as compared to topical steroids makes them particularly useful for pediatric and extended treatment regimens 49 . PDE‐4 controls cyclic adenosine monophosphate in immune and epithelial cells to modulate both the immune response and epithelial proliferation 50 .…”
Section: Nonsteroidal Topicalsmentioning
confidence: 99%